Pengembangan Model Pembelajaran Matematika SD Berbasis Permainan Tradisional Indonesia dan Pendekatan Matematika Realistik - Yohana Setiawan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This research was the first four parts of the Borg and Gall version of RnD research, (1) preliminary research and studies, (2) research planning, (3) initial product development, and (4) limited field testing. The purpose of this study is to explain the importance of using traditional games in teaching mathematics in elementary schools using a realistic mathematical approach. The method used is qualitative. Data obtained through interviews and teacher response scales. The subjects of this study were 15 elementary school teachers teaching elementary mathematics in Salatiga which were selected by purposive sampling technique. The results of this study is the steps to develop traditional games with a realistic mathematical approach in elementary mathematics learning.